Simulation of Static Loads on Multi-Purpose Electric Cargo Motor Frames: Simulation of Static Loads (Jurnal Rekayasa Mesin dan Inovasi Teknologi, 2023)
The frame should be the main focus in consideration for designing an electric motor. How powerful the electric motor is when carrying loads is all determined by the relationship between each dimension on the frame. In this study, we will make electric motor designs and static load simulations, especially on electric motor frames using 3D software. The purpose of this study is to get the value of stress misses simulation with CAD feature, Displacement value with CAD feature, and Get Safety Factor value with CAD feature. The research was conducted by conducting visual observations and taking the necessary technical data. The analysis of this work was carried out in the laboratory of Balikpapan University. The research method used is quantitative with the stage of literature studies that take reference sources for books, journals, and articles that support research in completing research. In this study, the independent variable is one that can be manipulated to observe its effect on the following variables. The purpose of this study is to get the value of simulation von misses stress with CAD feature Get the Displacement value with CAD feature Get the Safety Factor value with CAD feature. From the results of this study the simulation results of Von Misess Stress 43.185 N/mm2 with a given load of 1.274 N/mm2 which does not exceed the value of yield strength 250 N/mm2. Then. The result of the simulation of the largest displacement (maximum) = 0.117 mm and the smallest (minimum) = 0.001 mm, is said to be safe because it is far below the shift of 1 mm. And the value of the Safety factor results obtained is 5.704 N/mm2. This is said to be safe because it does not exceed the maximum value of the safety factor of 158,214 N/mm2. With safety standards that have been determined on the mechanical properties.